Wood Based Cellulose Nano Particles for Automotive Radiator - D., Ramasamy; K., Kadirgama; M. M., Rahman; M. M., Noor (Automotive Engineering Centre, 2016)
Wood based cellulose has abundant quantity in nature. It shows enhanced heat transfer and excellent physical properties, biodegradability, unique flow performance and liquid crystalline properties in suspensions and good heat transfer property and optical transparency (Dufresne, 2013). High efficiency on heat transfer is achieved by collaborative effect between nanocarbon and metal nanoparticles. The results show that the thermal conductivity of nanofluid is relevant to the type of filler and increases with the increasing of filler loading. A 27% enhancement in thermal conductivity is observed by adding only 0.5wt% of cellulose coated graphene nanoparticles in polyethylene glycol, and 49%, 40% and 30%. The nano cellulose coated metal nanofluid exhibit better stability after 14 days and no obvious sedimentation is observed. Compared with carbon coated Al and Fe nanoparticles, cellulose coated Graphene nanoparticles nanofluids have best stability and dispersibility and can efficiently enhance the thermal conductivity of base fluid. The usage in an automotive radiator system will enhance the heat transfer and has a potential to reduce the overall design size. Moreover, nanofluids stabilities are different when nanofluids were dispersed by three ways. Nanofluids dispersed by ball milling way possess the best stability, followed by nanofluids dispersed by ultrasonic dispersion way and magnetic stirring way.